Demokracja i religia w trosce o wartości - Szulakiewicz, Marek (Humaniora. Czasopismo Internetowe, 2023)
For quite a long time it was considered that it is the easiest to build democracy through the exclusion of religion and all religious content from the public sphere. This separation resulted in the crisis of religion that we experience nowadays and the degradation of democracy. The article is an attempt to rethink these relationships. It is pointed out that such a postulated separation, the exclusion of religion from the formation of the public sphere and participation in democracy, leads in this area to the subordination of everything to the majority rule, while with respect to religion per se to a dangerous religious fundamentalism. Religion provides the information that democracy cannot be limited only to institutions, procedures and the majority rule, but must also be rooted in the rules of law, the principle of justice and values. Religion is also important with respect to the condition of a democratic state and the fate of democracy. Democracy, on the other hand, is also of significant importance with regard to religion because it protects it from destructive fundamentalism.